UPAYA PENCEGAHAN OBESITAS PADA REMAJA MELALUI PENDIDIKAN KESEHATAN - Felndity, Bartol; Sahsun, Darmila; Saiful, Sinta; Musa, Sumianti; Lestari, Tutik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Obesity is a condition of excessive fat accumulation in the body due to an imbalance between incoming energy and energy used, which causes health risks. This community service activity aims to increase knowledge about obesity in adolescents. The method used is direct counseling with a powerpoint presentation, and using a questionnaire to measure participants' understanding. A total of 15 respondents participated in this activity and showed an increase in knowledge. The results showed that adolescents have a fairly good understanding of obesity. Therefore, it is hoped that adolescents can maintain a lifestyle in everyday life by implementing healthy behaviors to avoid various diseases and other health problems, one of which is obesity.